Theory to practice: a success in breeding sugarcane variety YZ08–1609 known as the King of Sugar - Wu, Qibin; Li, Aomei; Zhao, Peifang; Xia, Hongming; Zhang, Yuebin; Que, Youxiong (Frontiers in Plant Science, 2024)
Sugarcane, a significant cash crop in tropical and subtropical regions, contributes to 80% of sugar production and 40% of bioethanol production in the world. It is a key sugar crop, accounting for 85% of sugar production in China. Developing new varieties with high yield, high sugar, and better stress resistance is crucial for the sustainable growth of sugar industry. Hybrid breeding is the most widely used and effective method, with over 98% of Chinese sugarcane varieties resulting from this approach.Over the past two decades, Chinese breeders have developed the theory of high-heterogeneous composite high-sugar breeding, leading to the successful breeding of the fifth-generation sugarcane varieties. Among them, YZ08-1609, a complex hybrid of Saccharum spp., was developed by Sugarcane Research Institute (YSRI) of Yunnan Academy of Agricultural Sciences. The average cane yield of YZ08-1609 was 14.4% higher than ROC22. It is highly resistant to mosaic disease, and highly tolerant to drought stress, but moderately susceptible to smut disease. Notably, YZ08-1609 stands out with a sucrose content of 20.3%, setting an international record, earning the reputation as "King of Sugar". To summarize experience and inspire breeding, we provided here the detailed insights into the selection of parents, breeding process, and characteristics of YZ08-1609. Besides, the biological mechanisms underlying its high yield and high sugar was excavated at both transcriptional and metabolic levels. The challenges and prospects in breeding sugarcane varieties especially with high sugar were also discussed, offering a foundation for the future development of high-sugar varieties.